Strengthening Oversight : Improving the Quality of Statutory Audits in the Philippines - World Bank Group (World Bank, Washington, DC, 2016)
Since 2003, the Philippines have been striving to implement reforms aimed at improving audit quality. Oversight of the audit profession is a key control over the financial reporting architecture of a country’s private sector. A Quality Assurance Review system over audit practitioners is a subset of oversight which serves as a key monitoring control over the integrity of financial reporting. In keeping with the country’s strategic priority of boosting private sector development by improving the investment climate for firms of all sizes, including greater access to finance, legislation was enacted to support the objective of increasing the integrity of private sector financial reporting through improved audit quality. Accordingly, the Board of Accountancy was mandated with the power to conduct oversight into the quality of audits of financial statements through a review of the quality control measures instituted by auditors in order to ensure compliance with the accounting and auditing standards and practices. . However, the injunction remains in place and, accordingly, implementation of the mandated Quality Assurance Review Program may not move forward. Several concrete steps should be taken in order to effectively move forward with the rollout of a comprehensive system of public oversight including audit quality assurance in the Philippines. These include (1) reforming the legal framework to establish an effective audit oversight system with sufficient legal power and authority (2) rationalizing the statutory audit threshold to minimize the conditions contributing to low quality audits, (3) building support among key stakeholder groups by properly addressing their concerns to the extent possible, (4) ensuring coordination of efforts among regulators to eliminate gaps and overlaps and foster collaboration among the group, and (5) establishing a dedicated Project Management Office to oversee the rollout of a Quality Assurance Review Program over audit practitioners.